Gaussian Elimination By: Alberto Hernandez

First we have:

2y - 3z = 4
-2x + y + 2z = -6
2x + z = 0

R1 = R3 & R3 = R1

2 0 1 0
-2 1 2 -6
0 2 -3 4

R2 = R2 + R1

2 0 1 0
0 1 3 -6
0 2 -3 4

R3 = (-2)R2 + R3

2 0 1 0
0 1 3 -6
0 0 -9 16

Here we can already solve for z and do back substitution to get

our final answer, which are the following:

x = 8/9

y = -2/3

z = -16/9

- Alberto Hernandez

Unless otherwise stated, the content of this page is licensed under Creative Commons Attribution-ShareAlike 3.0 License